Genome‐wide association study reveals regions associated with gestation length in two pig populations. (14th December 2015) - Hidalgo, A. M.; Lopes, M. S.; Harlizius, B.; Bastiaansen, J. W. M.
Summary: Reproduction traits, such as gestation length (GLE), play an important role in dam line breeding in pigs. The objective of our study was to identify single nucleotide polymorphisms (SNPs) that are associated with GLE in two pig populations. Genotypes and deregressed breeding values were available for 2081 Dutch Landrace‐based (DL) and 2301 Large White‐based (LW) pigs. We identified two QTL regions for GLE, one in each population. For DL, three associated SNPs were detected in one QTL region spanning 0.52 Mbp on Sus scrofa chromosome (SSC) 2. For LW, four associated SNPs were detected in one region of 0.14 Mbp on SSC5. The region on SSC2 contains the heparin‐binding EGF‐like growth factor ( HBEGF ) gene, which promotes embryo implantation and has been described to be involved in embryo survival throughout gestation. The associated SNP can be used for marker‐assisted selection in the studied populations, and further studies of the HBEGF gene are warranted to investigate its role in GLE.